1) ответ: x = 11/2 =5 1/2
2) ответ: x = -3 1/8
Пошаговое объяснение:
-5/24x =-1 7/48
x = -55/48 ÷ (-5/24)
x = 11/2
ответ: x = 11/2 = 5 1/2
8 1/3÷x = -2 2/3
x= 8 1/3 ÷ (-2 2/3)
x = 25/3 ÷ (- 8/3)
x = 25/3 · (- 3/8)
x= - 25/8
x = - 3 1/8
ответ: x = -3 1/8
1) ответ: x = 11/2 =5 1/2
2) ответ: x = -3 1/8
Пошаговое объяснение:
-5/24x =-1 7/48
x = -55/48 ÷ (-5/24)
x = 11/2
ответ: x = 11/2 = 5 1/2
8 1/3÷x = -2 2/3
x= 8 1/3 ÷ (-2 2/3)
x = 25/3 ÷ (- 8/3)
x = 25/3 · (- 3/8)
x= - 25/8
x = - 3 1/8
ответ: x = -3 1/8